1984
DOI: 10.1126/science.6387910
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide Bond Engineered into T4 Lysozyme: Stabilization of the Protein Toward Thermal Inactivation

Abstract: By recombinant DNA techniques, a disulfide bond was introduced at a specific site in T4 lysozyme, a disulfide-free enzyme. This derivative retained full enzymatic activity and was more stable toward thermal inactivation than the wild-type protein. The derivative, T4 lysozyme (Ile3----Cys), was prepared by substituting a Cys codon for an Ile codon at position 3 in the cloned lysozyme gene by means of oligonucleotide-dependent, site-directed mutagenesis. The new gene was expressed in Escherichia coli under contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
149
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(154 citation statements)
references
References 35 publications
2
149
0
1
Order By: Relevance
“…Proteins can be engineered to be more stable in vitro with few mutations, by introduction of specific bonds (39,40) or favorable interactions (41)(42)(43). However, it has been shown that in vitro protein stabilization based on local stabilization of a secondary structural element can strengthen not only the final F state but also a small set of discrete partially folded native-like intermediates (41).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins can be engineered to be more stable in vitro with few mutations, by introduction of specific bonds (39,40) or favorable interactions (41)(42)(43). However, it has been shown that in vitro protein stabilization based on local stabilization of a secondary structural element can strengthen not only the final F state but also a small set of discrete partially folded native-like intermediates (41).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, the most extensively studied is T4 lysozyme, which has no disulfides in its native form. Five different novel disulfide bonds have been introduced into this protein (Perry & Wetzel, 1984;Wetzel et al, 1988;Matsumura et al, 1989a,b). Two have been found to lower T,,, by 20 "C at neutral pH.…”
Section: Novel Disulfidesmentioning
confidence: 99%
“…Increases in the conformational stability of a protein-desirable in many contexts (2)-can be realized by enhancing the hydrophobic effect (3, 4), introducing or shielding a hydrogen bond (5) or electrostatic interaction (6)(7)(8), or introducing a disulfide crosslink (9)(10)(11) or metal ion-binding site (12). These strategies are often frustrated by enthalpy-entropy compensation, whereby enthalpic stabilization is offset entirely by entropic destabilization, or vice versa (13).…”
mentioning
confidence: 99%